Paraquat Degradation by Biological Manganese Oxide (BioMnOx) Catalyst Generated From Living Microalga Pediastrum duplex AARL G060 - Thongpitak, Jakkapong; Pumas, Pamon; Pumas, Chayakorn (Frontiers in Microbiology, 2020)
Paraquat is a non-selective fast-acting herbicide used to control weeds in agricultural crops. Many years of extensive use has caused environmental pollution and food toxicity. This agrochemical degrades slowly in nature, adsorbs onto clay lattices, and may require environmental remediation. Studies have shown that biosynthesized manganese oxide (BioMnOx) successfully degraded toxic synthetic compounds such as bis-phenol A and diclofenac, thus it has potential for paraquat degradation. In this experiment, P. duplex AARL G060 generated low (9.03 mg/L) and high (42.41 mg/L) concentrations of BioMnOx. The precipitated BioMnOx was observed by scanning electron microscopy (SEM), and the elemental composition was identified as Mn and O by energy-dispersive x-ray spectroscopy (EDS). The potential for BioMnOx to act as a catalyst in the degradation of paraquat was evaluated under three treatments: (1) a negative control (deionized water), (2) living alga with low BioMnOx plus hydrogen peroxide, and (3) living alga with high BioMnOx plus hydrogen peroxide. The results indicate that BioMnOx served as a catalyst in the Fenton-like reaction that could degrade more than 50% of the paraquat within 72 h. A kinetic study indicated that paraquat degradation by Fenton-like reactions using BioMnOx as a catalyst can be described by pseudo-first and pseudo-second order models. The pH level of the BioMnOx catalyst was neutral at the end of the experiment. In conclusion, BioMnOx is a viable and environmentally friendly catalyst to accelerate degradation of paraquat and other toxic chemicals.